Analisis Kualitas Air dan Hubungannya dengan Pertumbuhan Ikan Lele Sangkuriang (Clarias gariepinus) pada Padat Tebar Berbeda - Kusuma, Ni Putu Dian; Tangguda, Sartika; Lau, Juniar Regina (Journal Galung Tropika, 2024)
Due to high demand, Sangkuriang catfish (Clarias gariepinus) is a widely cultivated consumption fish. This study aimed to analyze the relationship between water quality parameters such as temperature, pH, and water brightness with catfish growth. In addition, different stocking densities on catfish growth should be analyzed. The research was conducted at Omah Lele Catfish Farm from March to May 2023. The treatments consisted of Pond A, with a stocking density of 740 fish/m3, and Pond B, with a stocking density of 864 fish/m3. Growth data such as length, average body weight (ABW), and average daily growth (ADG) were analyzed using a T-test, and the relationship between water quality and growth was regression analysis. The interaction between temperature and catfish growth showed a negative/weak relationship, while the interaction between pH and water brightness on catfish growth was dominated by positive/strong. The stocking density variation of 740 fish/m3 showed better length and weight growth compared to the higher stocking density of 864 fish/m3.